2018
DOI: 10.7494/mafe.2018.44.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Additives on Electrodeposition of Tin From Acid Sulfate Solution

Abstract: Basic electrochemical experiments on the kinetics of tin deposition from an acid sulfate solution containing organic additives were performed. The measurements showed that tin deposits with activation polarization in a narrow potential range. Organic additives like gelatin and β-naphtol inhibit the charge transfer stage of the cathodic reaction due to the formation of adsorption layers. In turn, the gluconate ions increase the rate of tin deposition due to the bonding of hydrogen ions and inhibiting hydrogen c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…However, the wastewater from baths containing lead presents real environmental problems. To remedy this problem, several authors have suggested the addition of organic compounds 11,[14][15] or surfactants 12,16-17, which can play the same role as lead. Some efforts have been made to develop appropriate additives and to discover their modes of intervention in the deposition kinetics and thus their impact on the morphological properties and structure.…”
Section: Introductionmentioning
confidence: 99%
“…However, the wastewater from baths containing lead presents real environmental problems. To remedy this problem, several authors have suggested the addition of organic compounds 11,[14][15] or surfactants 12,16-17, which can play the same role as lead. Some efforts have been made to develop appropriate additives and to discover their modes of intervention in the deposition kinetics and thus their impact on the morphological properties and structure.…”
Section: Introductionmentioning
confidence: 99%